Evaluating the Effect of Painting Therapy on Happiness in the Elderly - Hamid Barfarazi; Tayabe Pourghaznein; Samira Mohajer; Seyed Reza Mazlom; Seyed Mohsen Asgharinekah (Mashhad University of Medical Sciences, 2018)
Background: Reduced happiness is one of the consequences of aging. Happiness is a component of mental health that leads to life satisfaction and physical well-being. Aim: This study aimed to evaluate the effect of painting therapy on the happiness of the elderly. Method: This randomized clinical trial was conducted on 60 elderlies in 2017. The subjects were selected from two elderly care centers in Mashhad, Iran, through the convenience sampling method and randomly divided into two groups of intervention (N=30) and control (N=30). The data collection tools included a demographic characteristics form, research unit selection questionnaire, Cognitive Short Questionnaire, and Oxford Happiness Questionnaire. In addition, 12 sessions of painting therapy (three 50-60-minute sessions per week) were performed. At the end of the intervention, the Oxford Happiness Questionnaire was completed again by the subjects of both groups. In addition, data analysis was performed in SPSS, version 21. Results: In this study, the groups were homogenous in terms of demographic variables. In terms of mean happiness score before the intervention, no significant difference was observed between the intervention and control groups (55.6±2.1 vs. 57.6±5.0; P=0.06). However, after the intervention, the mean score of happiness was significantly higher in all its dimensions in the intervention group compared to the control group (P